Encyclopedia of Analytical Chemistry 2000
DOI: 10.1002/9780470027318.a2037
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetry of Polymers

Abstract: Thermogravimetry (TG) is the study of the relationship between a sample's mass and its temperature. It can be used to study any physical (such as evaporation) or chemical process (such as thermal degradation) that causes a material to lose volatile gases. Polymers have different thermal stabilities and thus the qualitative “fingerprint” afforded by TG in terms of temperature range, extent and kinetics of decomposition provides a rapid means to distinguish one polymer from another using only milligram quantitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
0
11
0
7
Order By: Relevance
“…The decomposition of the polymers can be analyzed, indicating weight loss of the sample or water evaporation 33 . The TGA results are analyzed in Figure 4.…”
Section: Dsc/tgamentioning
confidence: 99%
“…The decomposition of the polymers can be analyzed, indicating weight loss of the sample or water evaporation 33 . The TGA results are analyzed in Figure 4.…”
Section: Dsc/tgamentioning
confidence: 99%
“…Besides, the chemical shifts of C-2,3,5 signals in the spectra of β-CD/PCL100 and β-CD/PLA100 polymeric samples were altered compared to native β-CD. The thermogravimetric analysis (TGA) of polymers primarily provides information about thermal stability, and then, it allows to find out the decomposition mechanisms for the investigated materials [ 35 ]. TGA was carried out to investigate the influence of the β-CD incorporation on the thermal stability of the obtained polymers.…”
Section: Resultsmentioning
confidence: 99%
“…By extending the study beyond 24 dpa, the maturation process of the developing cotton fibers was studied as well. Thus, fibers were harvested at 10,14,17,18,19,20,21,22,23,24,27,30,36,46, and 56 dpa. Figure S1 shows the list of samples.…”
Section: Methodsmentioning
confidence: 99%
“…Thermogravimetry is the study of the relationship between the mass of a sample and its temperature, and it can be used to study physical and chemical processes, e.g., degradation. TGA can be used for quantitative compositional analysis of polymers, lifetime prediction, and kinetic analysis [23]. Abidi et al [24] reported relationships between cotton fiber micronaire, maturity, and fineness, and their thermal degradation properties.…”
Section: Introductionmentioning
confidence: 99%